The Relationship between Critical Thinking and Digital Leadership on Employee Performance through Strengthening Organizational Culture at Universitas Muhammadiyah Aceh: Hubungan antara Berpikir Kritis dan Kepemimpinan Digital terhadap Kinerja Karyawan melalui Penguatan Budaya Organisasi di Universitas Muhammadiyah Aceh - Haru Firdaus; Febyolla Presilawati; Surna Lastri (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
This study examines the role of organizational culture in mediating the influence of critical thinking and digital leadership on employee performance at the University of Muhammadiyah Aceh. Digital transformation demands that organizations have adaptive and innovative human resources, where critical thinking and digital leadership are key competencies expected to improve performance directly or through strengthening organizational culture. This study used a quantitative approach with a survey design and Structural Equation Modeling (SEM) analysis of 205 respondents who were all permanent employees of the university. The variables tested included critical thinking and digital leadership as independent variables, organizational culture as a mediating variable, and employee performance as a dependent variable. The results showed that critical thinking and digital leadership did not have a significant direct effect on employee performance, but both had a significant positive effect on organizational culture, which in turn had a significant effect on performance. Organizational culture was proven to partially mediate the relationship between critical thinking and digital leadership with employee performance. This finding emphasizes the importance of strengthening an adaptive and innovative organizational culture as a key pillar of performance improvement in the digital era. Practically, the research recommends the development of critical thinking training programs, improving digital leadership competencies, and strengthening a work culture that aligns with the university's vision and mission, as well as providing theoretical contributions to digital-based human resource management in higher education.